Kajian Alam Semesta Dalam Sudut Pandang Al-Qur’an Dan Sains Modern - Usman (Jurnal Mediasas: Media Ilmu Syari'ah dan Ahwal Al-Syakhsiyyah, 2024)
This journal explains the relationship between the Quran, science, and the concept of the universe. The research was conducted to understand the concept of the universe from the perspective of the Quran and science. This study is a literature review using the methods of Quranic interpretation and thematic analysis, which involves gathering readings that discuss the human senses, determining a topic, conducting analysis with tahlili interpretation, and drawing conclusions. As a result, all concepts of the universe discovered by scientists have already been written and conveyed by Prophet Muhammad SAW 1,400 years ago in the Holy Quran. The Quran is always ahead of science, but it is not a science textbook; rather, it is a guide for humanity in navigating the three dimensions of life: the worldly life, the barzakh (the interim state between death and the afterlife), and the hereafter. Jurnal ini menjelaskan tentang hubungan antara Al-Quran dan ilmu pengetahuan serta konsep alam semesta. Penelitian ini dilakukan untuk mengetahui konsep alam semesta menurut pandangan Al-Qur’an dan sains. Penelitian ini merupakan penelitian kepustakaan dengan menggunakan metode tafsir Al-qur’an dan tematik, yaitu mengumpulkan bacaan yang berbicara tentang panca indera manusia, menentukan topik dan melakukan analisis dengan tafsir tahlili, dan menarik kesimpulan. Alhasil semua konsep alam semesta yang ditemukan oleh ilmuwan sudah tertulis dan disampaikan oleh Nabi Muhammad SAW 1400 tahun yang lalu dalam kitab suci Al-Quran. Al-Quran selalu lebih terdepan dari pada sains, tapi Al-Quran bukan buku pelajaran sains, tapi Al-Quran merupakan penuntun bagi umat manusia dalam mengarungi ketiga dimensi kehidupan, yaitu dimensi alam fana, barzakh dan akhirat.